A DIGITALIZATION MODEL FOR NEW STUDENT ADMISSION SERVICES THROUGH A WEB-BASED INFORMATION SYSTEM IN PRIMARY SCHOOLS - Arif Rahman; Arabiatul Adawiyah; Surahmat surahmat; Delta Khairunnisa; Rahul Sabilillah; Panisah Panisah; Zalsabila Herawaty (Bulletin of Network Engineer and Informatics, 2026)
Digital transformation in education has encouraged schools to modernize administrative services, including new student admissions. However, many primary schools still rely on manual registration processes that often lead to inefficiencies, data inaccuracies, and limited access to information. This study aims to develop a digitalization model for new student admission services through a web-based information system in primary schools. A qualitative case study was conducted at SD Islam Al-Asri Palembang using observation, semi-structured interviews, and documentation techniques. The study employed a prototype-based development approach to analyze existing admission processes and formulate a digitalization model that integrates registration, data management, verification, and reporting services. Model validation was carried out through practitioner review involving the school principal, administrative staff, and IT personnel, using three evaluation parameters: model practicality, completeness of the five service components, and contextual applicability within the primary school setting. The results show that the proposed model consists of five key components: digital registration, data validation, document management, admission status notification, and reporting services. The model simplifies administrative workflows, improves data accuracy, accelerates the admission process, and enhances transparency and accessibility for both parents and school administrators. The study concludes that the proposed digitalization model can support the modernization of primary school admission services and serve as a replicable reference for schools seeking to implement digital transformation in educational administration.